Somewhere different to go: Report from SiMERR Western Australia - Frid, Sandra; Sparrow, Len; Trinidad, Sue; Treagust, David; McCrory, Kirsteen (DEST, 2006)
Western Australia is a state of 2.5 million square kilometres with only about 400,000 people outside the Perth metropolitan area. The distances are great, the population is sparse, and people live and work in a wide range of geographic and socio-economic environments. There are desert regions and isolated mining sites with daily temperatures that can soar up to 50 degrees, while there are also lush forests, agricultural lands, and seaside resort communities. The capital city, Perth, is known as the most isolated capital city in the world, so that, even with a population of over 1.2 million, it is a city characterised by physical separation from other populated centres. Yet, as one travels away from Perth within Western Australia, there is much diversity and richness in the social, cultural, economic and physical environments. It is in this context that this chapter is written.